4(n-3)-3n=1+2

Simple and best practice solution for 4(n-3)-3n=1+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(n-3)-3n=1+2 equation:


Simplifying
4(n + -3) + -3n = 1 + 2

Reorder the terms:
4(-3 + n) + -3n = 1 + 2
(-3 * 4 + n * 4) + -3n = 1 + 2
(-12 + 4n) + -3n = 1 + 2

Combine like terms: 4n + -3n = 1n
-12 + 1n = 1 + 2

Combine like terms: 1 + 2 = 3
-12 + 1n = 3

Solving
-12 + 1n = 3

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 1n = 3 + 12

Combine like terms: -12 + 12 = 0
0 + 1n = 3 + 12
1n = 3 + 12

Combine like terms: 3 + 12 = 15
1n = 15

Divide each side by '1'.
n = 15

Simplifying
n = 15

See similar equations:

| cos^2x+5cosx=1 | | 15x-17=22 | | 10+7f=8f | | 2x+18=-3y | | 3*(5*x-7)+2*(2*x+17)=5*(3*x-4)+37 | | (3y-5)(8-y)=0 | | 4(x)=3x-1 | | X^2+x=0.24 | | 3(1)-2(6)=9 | | 5x+1=-16 | | 6(y+2)=-3(6y-1)+6y | | 13X=10X-9 | | Y=-x(x-2) | | 3(1)+2(6)=9 | | 3x^2+5x-2y^2=0 | | -x(0)+5y=15 | | -x+0=15 | | 2y-42=4 | | a+4-a(a+4)=0 | | 5h+24=-8(b-6)+6b | | sin(x)=0.5625 | | 1a-4b+2c=0 | | 8p=9 | | 2+19=43 | | sinx=0.5625 | | x(x-8)+2(x-8)=0 | | 5+3y=9 | | Y=5x^2+35 | | z-34.7=68.2 | | 10x+8y+z=100 | | 6x-30=6x+12 | | 5ln(x^2)=4ln(x^3)+6 |

Equations solver categories